2022
DOI: 10.3390/insects13030252
|View full text |Cite
|
Sign up to set email alerts
|

Similar Bacterial Communities among Different Populations of a Newly Emerging Invasive Species, Tuta absoluta (Meyrick)

Abstract: Microorganisms in the guts of insects enhance the adaptability of their hosts with different lifestyles, or those that live in different habitats. Tuta absoluta is an invasive pest that is a serious threat to tomato production in China. It has quickly spread and colonized Xinjiang, Yunnan and other provinces and regions. We used Illumina HiSeq next generation sequencing of the 16S rRNA gene to study and analyze the composition and diversity of the gut microbiota of three geographical populations of T. absoluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
5
8
0
Order By: Relevance
“…However, Ramalho et al (2017) discovered that host phylogeny can affect the total bacterial community of spiny ants, while geographic source had no effect. Similar bacterial communities were observed among different populations of Tuta absoluta (Meyrick) (Wang et al, 2022). The gut microbial , 2018).…”
Section: Discussionsupporting
confidence: 55%
“…However, Ramalho et al (2017) discovered that host phylogeny can affect the total bacterial community of spiny ants, while geographic source had no effect. Similar bacterial communities were observed among different populations of Tuta absoluta (Meyrick) (Wang et al, 2022). The gut microbial , 2018).…”
Section: Discussionsupporting
confidence: 55%
“…Cnaphalocrocis medinalis (Pyralidae) (Y. J. Yang et al, 2020), Adelphocoris suturalis (Miridae) (Xue et al, 2021), Ips typographus (Scolytidae) (Fang et al, 2020), Tuta absoluta (Meyrick) (H. Wang et al, 2022). Proteobacteria and Firmicutes were widely present in different insect taxa and in high abundances which is expected as they was reported to be associated with host environmental adaptation, digestion, nutrient supply, and energy metabolism (Cao et al, 2021;B.…”
Section: Discussionmentioning
confidence: 95%
“…Our results agree with that of (Schloss et al, 2006) who identified that Proteobacteria and Firmicutes are two abundant bacteria phylum in A. glabripennies . Similar results were found across different taxa of insect, such as Monochamus alternatus and Psacothea hilaris (Cerambycidae) (Kim et al, 2017), Rhynchophorus ferrugin (Muhammad et al, 2017), Popillia japonica (Scarabaeidae) (Chouaia et al, 2019), Cnaphalocrocis medinalis (Pyralidae) (Y. J. Yang et al, 2020), Adelphocoris suturalis (Miridae) (Xue et al, 2021), Ips typographus (Scolytidae) (Fang et al, 2020), Tuta absoluta (Meyrick) (H. Wang et al, 2022). Proteobacteria and Firmicutes were widely present in different insect taxa and in high abundances which is expected as they was reported to be associated with host environmental adaptation, digestion, nutrient supply, and energy metabolism (Cao et al, 2021; B. S. Chen et al, 2016; Fonknechten et al, 2010; Martinez et al, 2019; Mohammed et al, 2018; Suen et al, 2010; Yun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…with food digestion, nutrition absorption, defense responses to pathogens, and xenobiotic metabolism, while also promoting insect development and reproduction [8,9]. For example, the fungal-yeast-like symbiotes in planthoppers and aphids are vital for the synthesis of essential amino acids and for maintaining the vitamin supply in the insect host [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…During the interaction between microbial symbionts and insects, the insects provide the habitat and nutrition for microbes, and in return, these symbionts help the host insects with food digestion, nutrition absorption, defense responses to pathogens, and xenobiotic metabolism, while also promoting insect development and reproduction [ 8 , 9 ]. For example, the fungal-yeast-like symbiotes in planthoppers and aphids are vital for the synthesis of essential amino acids and for maintaining the vitamin supply in the insect host [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%